2018
DOI: 10.4103/jcd.jcd_320_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retention and fracture resistance of different fiber reinforced posts: An in vitro study

Abstract: Aim:The aim of this study was to evaluate retention & fracture resistance of different fibre posts.Methodology:90 extracted human permanent maxillary central incisors were used in this study. For retention evaluation, after obturation, post space preparation was done in all root canals and posts were cemented under three groups. Later, the posts were grasped & pulled out from the roots with the help of a three-jaw chuck at a cross-head speed of 5mm/min. Force required to dislodge each post was recorded in Newt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…From this study we found that maximum fracture resistance was observed with zirconia posts. Pruthi et al (2018) assessed the fracture resistance of different fiber reinforced posts and concluded that, parallel posts to have better retention than tapered and double tapered posts [ 1 ]. Saritha et al (2017) evaluated the fracture resistance of carbon, zirconia and glass fiber post and found that zirconia had good fracture resitance similar to our results [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this study we found that maximum fracture resistance was observed with zirconia posts. Pruthi et al (2018) assessed the fracture resistance of different fiber reinforced posts and concluded that, parallel posts to have better retention than tapered and double tapered posts [ 1 ]. Saritha et al (2017) evaluated the fracture resistance of carbon, zirconia and glass fiber post and found that zirconia had good fracture resitance similar to our results [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esthetics and structural durability plays a major role in treatment outcome of endodontically treated teeth. There has been an increased demand for endodontic post and core materials for destructed endodotically treated teeth [ 1 ]. Teeth with crown structure less than 50% can be restored with post and core.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 38 ] The parallel-sided serrated posts also show better retention compared to tapered posts and double tapered posts. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, for standardization, parallel posts space was prepared which probably deprived additional mechanical retention provided by small undercuts present in the canal therefore, prefabricated serrated parallel side posts (both carbon and glass fiber post) were used, which provided additional retentive features, as they get embedded into the resin luting cement and resist dislodging forces on pulling. [813]…”
Section: Discussionmentioning
confidence: 99%